The influence of temperature on adsorption capacity of Malaysian coal - Azmi, Azlin Suhaida; Yusup, Suzana; Muhamad , Suhana (Elsevier, 2006)
The paper highlights the study of carbon dioxide (CO2) adsorption profiles of local coal samples of varying mean size distributions (1000 and 2000m) obtained from Miri, Sarawak situated in the East of Malaysia, at different temperatures (24.6, 30, 40 and 55 ◦C). Parameters such as the moisture content, ash content, carbon content and mineral content of the coal sample are investigated. Based on the physical analysis of the coal, it was classified as lignite, which exhibits a better adsorptive capability of CO2. In addition, the coal sample having the smaller mean particle size distribution of 1000m shows a better rate of adsorption compared to the 2000 m size distribution. The adsorption capacity of the coal sample shows an inverse relationship with temperature. These findings open a platform for CO2 sequestration to be implemented in Malaysia. © 2005 Elsevier B.V. All rights reserved.